Assessing mitochondria biogenesis - Medeiros, Denis M. (My University, 2008)
Mitochondria have their own DNA (mtDNA) and hence biogenesis of mitochondria requires a coordination of nuclear and mtDNA, both of which encode for mitochondria proteins. Our understanding of the molecular control of mitochondria biogenesis has increased in recent years, providing key signatures of the process. To determine whether or not a tissue or an organ of human or animal origin is undergoing mitochondria biogenesis, multiple parameters should be analyzed. First and foremost is visualization and measurement of mitochondria mass/volume in histological sections using fluorescent mitochondria dyes and light microscopy or transmission electron microscopy to yield quantitative results. To confirm or extend these types of analysis, biochemical markers of mitochondria biogenesis should also be included, including assessment of mtDNA copy number, steady-state levels of biogenesis-related transcription factors (e.g. mitochondria transcription factor A, mitochondrial transcription specificity factors, nuclear respiratory factors 1 and 2, and peroxisome proliferator activated receptor gamma coactivator-1-alpha), mtDNA-encoded transcripts and proteins, and rates of mitochondria translation. These techniques are described in isolation and in the context of transgenic and dietary animal models that have been used as tools to study the regulation of mitochondria biogenesis and its role in disease pathology.
Keywords: Mitochondria; Biogenesis; Electron microscopy; PGC-1alpha; Mitochondria transcription factors; Morphometry